Análise do processo de amortecimento de cheias em reservatórios: parâmetros intervenientes e proposta de método de estimativa - Souza, Danilo Nogueira de (2014)
Flood damping constitutes a fundamental characteristic of surface reservoirs, because it has direct impact on the safety of the dam itself, affecting other functions of the dam. So, if this feature is not efficient enough to attenuate the peak inflow, there is a serious risk of occurrence of "overtopping”; in other words, the height of the poured water exceeds the maximum value allowed in the project. Many surface reservoirs are getting old and out of the current technical standards, being worrying the situation in the State of Ceará, in which several dams were built more than half a century ago. This fact is particularly important, given that these reservoirs play multiple roles. Thus, to ensure that brazilians dams’ minimum safety standards are met, The Dams Act was approved in 2010. This law appeared in response, as in many countries, to the occurrence of significant types of accidents, including the ones resulting from “overtopping”. Therefore, in order to more detail the process of flood damping in semiarid reservoirs, hydrological simulations were performed for several scenarios that represent settings of reservoirs and watersheds through the variation of the original parameters of a test reservoir (João Guerra Dam). As a result, it was determined the weight of each dimensionless physical parameter and each variable in the flood damping. These parameters were aggregated into a single index, in whose function it was proposed an easy expeditious graphical method in order to estimate the flood damping, according to different values of precipitation. This study also revealed that the decamillennial damping, from a given fraction of precipitation, can be approximated by the millennial damping, and the method is more sensitive to the variation of the form factor of the reservoir than to the variations of the other variables.